14
$\begingroup$

$\newcommand{\id}{\operatorname{Id}}$ $\newcommand{\TM}{\operatorname{TM}}$ $\newcommand{\Hom}{\operatorname{Hom}}$ $\newcommand{\M}{\mathcal{M}}$ $\newcommand{\N}{\mathcal{N}}$ $\newcommand{\tr}{\operatorname{tr}}$ $\newcommand{\TM}{\operatorname{T\M}}$ $\newcommand{\TN}{\operatorname{T\N}}$ $\newcommand{\TstarM}{T^*\M}$

Edit: I narrowed the focus of the question.

Summary: I suspect $\delta(df \wedge df)=0$ is not an E-L equation because it pus too many constraints on $f$. Can this heuristic be formalized?

Let $\M,\N$ be $d$-dimensional oriented Riemannian manifolds, and let $f:\M \to \N$ be smooth; $df \in \Omega^1(\M,f^*{\TN})$, and for $1 < k \le d$ let $\bigwedge^k df\in \Omega^k\big(\M,\Lambda_k(f^*{\TN})\big)$ be the induced map.

Notation:

$\nabla^{\Lambda_k(f^*{\TN})}$ is the induced connection on $\Lambda_k(f^*{\TN})$, $\delta_{\nabla^{\Lambda_k(f^*{\TN})}} $ is the adjoint of $d_{\nabla^{\Lambda_k(f^*{\TN})}}$.

Question: Is $\delta_{\nabla^{\Lambda_k(f^*{\TN})}} \big( \bigwedge^k df \big) =0$ an Euler-Lagrange equation of some functional $E(f)$?

I suspect the answer is negative.

Edit: Can this be proved using known results on inverse problems in calculus of variations? e.g if we can show the equation in the Euclidean setting ($M=N=\mathbb{R}^d$) is not an E-L eq, then we are done.

(I am not aware of much work on such inverse problems in general Riemannian settings, but if the Euclidean can be decided, it's enough).

Heuristic:

$\delta_{\nabla^{\Lambda_k(f^*{\TN})}} \big( \bigwedge^k df \big) =0$ puts too many constraints on $f$:

$\delta_{\nabla^{\Lambda_k(f^*{\TN})}} \big( \bigwedge^k df \big) \in \Omega^{k-1}(\M,\Lambda_k(f^*{\TN}))$, so locally the "equation" is a system of ${d \choose k-1}{d \choose k}$ scalar equations.

However, it seems to me an Euler-Lagrange eq of a functional cannot consist of more than $\dim(f^*\TN)=d$ equations, since (roughly) this is the number of degrees of freedom we have in choosing the variation field $V\in\Gamma(f^*\TN)$.

More explicitly, since $dE(V)$ is linear in $V$, it should always be in the form of $dE(V)=\langle A(f),V \rangle$, where $A(f) \in \Gamma(f^*\TN)$ so the E-L eq should be in the form of $A(f)=0$.

Of course, this argument gives only an upper bound to the number of "independent" constraints - degeneracies can occur (e.g Null-Lagrangians).

So, suppose ${d \choose k-1}{d \choose k}>d$. Is it possible $\delta_{\nabla^{\Lambda_k(f^*{\TN})}} \big( \bigwedge^k df \big) =0$ is degenerate and reduces to no more than $d$ independent eqs (locally)?

Can we prove this is not happening? (If we can, than this shows our equation is not an E-L eq of any functional).


Analysis of the borderline cases:

We now turn to see what happens when ${d \choose k-1}{d \choose k}=d$. This happens (for $1 \le k \le d$) iff $k=1$ or $k=d$. The former corresponds to harmonicity. Suppose that $k=d$. We will try to understand if our equation is an E-L equation in this case.

For concreteness, let's work with $k=d=2$.

I proved in my answer that the E-L equation of the functional $$ E_2(f)=\frac{1}{2}\int_{M} \| \bigwedge^2 df\|^2 \text{Vol}_{M}, \, \text{is}$$ $$h_{f^*\TN} \big( \tr_{\TM}\big( df \otimes \delta_{\nabla^{\Lambda_2(f^*{\TN})}}(\bigwedge^2 df)\big) \bigg)=0.$$ Since $h_{f^*\TN}$ is injective in this case, the E-L eq is equivalent to $$\tr_{\TM}\big( df \otimes \delta_{\nabla^{\Lambda_2(f^*{\TN})}}(\bigwedge^2 df)\big)=0. \tag{1}$$

When restricting the discussion to immersions, this reduces to $ \delta_{\nabla^{\Lambda_2(f^*{\TN})}}(\bigwedge^2 df)=0$.

It is not clear what happens in the general case; If we don't assume $f$ is an immersion, are the equations equivalent? (If not, perhaps there is another way to realize $\delta_{\nabla^{\Lambda_2(f^*{\TN})}}(\bigwedge^2 df)=0$ as an E-L eq).

The problem is that we cannot conclude (at least not immediately) that at every point where $df$ is not invertible, $\delta_{\nabla^{\Lambda_2(f^*{\TN})}}(\bigwedge^2 df)=0$. (We know $\bigwedge^2 df=0$ at the point, but $\delta$ is a differential operator, it sees beyond the pointwise behaviour).

$\endgroup$
4
$\begingroup$

Consider the following functional:

$$ E_k(f)=\frac{1}{2}\int_{M} \| \bigwedge^k df\|^2 \text{Vol}_{M}.$$

Theorem:

The Euler-Lagrange equation of $E_2$, is $A(\phi)=0$, where $A(\phi) \in \Gamma(\phi^*\TN)$ is defined by

$$ A(\phi)=h_{\phi^*TN}\bigg(\tr_{\TM}\big(d\phi \otimes \delta_{\nabla^{\Lambda_2(\phi^*{\TN})}}(d\phi \wedge d\phi)\big)\bigg).$$

$$h_{\phi^*TN}:\phi^*TN \otimes \Lambda_2(\phi^*TN) \to \phi^*TN$$ is a linear map, which depend on the metric on $\N$, and is defined precisely below (see eq $(6)$, and replace $W$ with $\phi^*TN$).

Proof:

Let $\phi$ be a map $\M \to \N$, and $\phi_t:\M \to \N$ as smooth family, where $\phi_0=\phi$ and $\frac{\partial \phi_t}{\partial t}|_{t=0}:=V \in \Gamma(\phi^*(\TN))$. Then

$$ \frac{d}{dt}|_{t=0}E(\phi_t)=\frac{1}{2}\int_{\M}\frac{\partial{}}{dt}|_{t=0} \| d\phi_t \wedge d\phi_t \|^2 \text{Vol}_{\M}= \int_{\M} \langle d\phi \wedge d\phi, \nabla_{\frac{\partial{}}{dt}} (d\phi_t \wedge d\phi_t)|_{t=0}\rangle \text{Vol}_{\M}. \tag{1}$$

It is well-known that $\nabla_{\frac{\partial{}}{dt}} d\phi_t|_{t=0}=\nabla^{\phi^*(TN)}V \in \Gamma(T^*\M \otimes \phi^*(\TN))$.

Now,

$$\bigg(\nabla_{\frac{\partial{}}{dt}} (d\phi_t \wedge d\phi_t)|_{t=0}\bigg)(X,Y)=$$ $$(\nabla_{\frac{\partial{}}{dt}} d\phi_t|_{t=0})(X) \wedge d\phi(Y)+d\phi(X) \wedge (\nabla_{\frac{\partial{}}{dt}} d\phi_t|_{t=0})(Y)=$$

$$ \nabla V(X)\wedge d\phi(Y)+d\phi(X) \wedge \nabla V(Y)= $$

$$\big(\nabla V \wedge d\phi+d\phi \wedge \nabla V\big) (X,Y), \tag{2}$$

where $\nabla V \wedge d\phi+d\phi \wedge \nabla V \in \Omega^2\Big(\M,\Lambda_2 \big(\phi^*T\N\big)\Big)$ is defined by the last equality.

Thus, we have obtained

$$ \nabla_{\frac{\partial{}}{dt}} (d\phi_t \wedge d\phi_t)|_{t=0}= \nabla V \wedge d\phi+d\phi \wedge \nabla V. \tag{3}$$

Define also $\xi=V \wedge d\phi \in \Omega^1\Big(\M,\Lambda_2 \big(\phi^*T\N\big)\Big)$.

Lemma: $d_{{\nabla}^{\Lambda_2(\phi^*T\N)}}(\xi)=\nabla V \wedge d\phi+d\phi \wedge \nabla V$.

Assuming the lemma, we combine equations $(1),(3)$ and get

$$ \frac{d}{dt}|_{t=0}E(\phi_t)=\int_{\M} \langle d\phi \wedge d\phi, d_{{\nabla}^{\Lambda_2(\phi^*T\N)}}(\xi)\rangle \text{Vol}_{\M}=\int_{\M} \langle \delta_{\nabla^{\Lambda_2(\phi^*{\TN})}}(d\phi \wedge d\phi),\xi\rangle \text{Vol}_{\M}. \tag{5}$$

To find the exact $E-L$ equations, one further step needs to be taken: $$V \to \langle \delta_{\nabla^{\Lambda_2(\phi^*{\TN})}}(d\phi \wedge d\phi),\xi\rangle=\langle \delta_{\nabla^{\Lambda_2(\phi^*{\TN})}}(d\phi \wedge d\phi),V \wedge d\phi\rangle$$ is a linear functional in $V$, so it can be expressed as $V \to \langle V, A(\phi) \rangle_{\phi^*\TN}$,

where $A(\phi) \in \Gamma(\phi^*\TN)$. The E-L equation is $A(\phi)=0$.

We now turn to finding an explicit expression for this "representation":

The corresponding pointwise linear algebra situation is this:

We have two oriented $d$-dimensional inner product spaces $V,W$, together with maps $A \in \Hom(V,W),B \in \Hom(V,\Lambda_2(W))$, and we look for a bilinear map $$\psi: \Hom(V,W) \times \Hom(V,\Lambda_2(W)) \to W,$$ satisfying

$$ \langle w \wedge A,B \rangle_{\Hom(V,\Lambda_2(W))}=\langle w, \psi(A,B) \rangle_W \, \text{ for every $w \in W$}$$

Proposition: With the notation as above, $\psi(A,B)=h_W\big(\tr_{V} (A \otimes B)\big)$ where $h_W:W \otimes \Lambda_2(W) \to W$ is defined by the linear extension of

$$ \tilde w \otimes (w_1 \wedge w_2) \to \langle \tilde w,w_2 \rangle w_1-\langle \tilde w,w_1 \rangle w_2. \tag{6}$$

Note $A \otimes B \in V^* \otimes V^* \otimes W \otimes \Lambda_2(W)$, so $\tr_{V} (A \otimes B) \in W \otimes \Lambda_2(W)$.

Proof:

It suffices to prove this for $A,B$ "pure" tensors, i.e $A=\alpha \otimes \tilde w,B=\beta \otimes (w_1 \wedge w_2)$, where $\alpha,\beta \in V^*,\tilde w,w_1,w_2 \in W$.

Now, on the one hand

$$ \langle w \wedge A,B \rangle_{\Hom(V,\Lambda_2(W))}= \langle \alpha \otimes (w \wedge \tilde w) ,\beta \otimes (w_1 \wedge w_2) \rangle_{\Hom(V,\Lambda_2(W))}=$$

$$ \langle \alpha , \beta \rangle_{V^*} \langle w \wedge \tilde w ,w_1 \wedge w_2 \rangle_{\Lambda_2(W)}. $$

On the other hand

$$ \tr_{V} (A \otimes B)= \langle \alpha , \beta \rangle_{V^*} \tilde w \otimes (w_1 \wedge w_2).$$

Thus, it's enough to show

$$ \langle w \wedge \tilde w ,w_1 \wedge w_2 \rangle_{\Lambda_2(W)}=\langle w , h_W\big(\tilde w \otimes (w_1 \wedge w_2)\big) \rangle_W,$$

but this nows follows directly form the definition of the induced inner product on $\Lambda_2(W)$, and the definition of $h_W$ (see $(6)$).

Using the above proposition, we deduce that $$ A(\phi)=h_{\phi^*TN}\bigg(\tr_{\TM}\big(d\phi \otimes \delta_{\nabla^{\Lambda_2(\phi^*{\TN})}}(d\phi \wedge d\phi)\big)\bigg).$$


| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.